STUDIES ON ANTICONVULSANT ACTIVITY OF ANNACYCLUS PYRETHRUM IN ALBINO MICE - D, Nirmala (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: A study which involves in detecting anticonvulsant activity from Anacyclus pyrethrum roots by using maximal electroshock seizure (MES) in a dose-dependent way with the production of ethanolic extraction. Methods: The MES test is considered to be a predictor of likely therapeutic efficacy against generalized tonic-clonic seizures. Results: MES-induced tonic seizures can be prevented either by drugs that inhibit voltage dependent Na+ channels, such as phenytoin, valproate, and lamotrigine or by drugs that block glutamatergic excitation mediated by the N-methyl-D-aspartate receptor like felbamate. Conclusion: The efficiency of A. pyrethrum will be detected after the incubation time of the animal, and the values of the ethanolic extraction will be tested for the anticonvulsant activity. Keywords: Anacyclus pyrethrum, Albino mice, Maximal electroshock seizure, Anticonvulsant activity, Drugs.